High-entropy monatomic / cluster-loaded carbon nanofiber oxygen catalyst and preparation method thereof

The preparation of high-entropy single atom/cluster carbon nanofiber oxygen catalysts is solved through electrospinning and high-temperature carbonization technology, and the kinetics and stability of the positive electrode of zinc-air batteries is achieved, achieving low-cost and efficient catalytic activity and stability , suitable for the development of flexible energy storage devices.

CN119208634AActive Publication Date: 2024-12-27SUZHOU UNIV

Patent Information

Application Number
CN202411697485.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-26
Publication Date
2024-12-27
Estimated Expiration
2044-11-26

AI Technical Summary

Technical Problem

The ORR and OER reaction kinetics of existing zinc-air battery positive electrodes are slow, the cycle stability is poor, and precious metal catalysts are costly and scarce, making it difficult to achieve efficient and stable bifunctional oxygen catalysts.

Method used

Electrospinning, high-temperature carbonization and chemical vapor deposition technology were used to prepare high-entropy single atom/cluster carbon nanofiber oxygen catalysts, and through uniform anchoring of transition metals such as Zn, Co, Ni, and Cu, microstructures with multi-stage pore structures were formed. Nanocarbon fibers achieve high catalytic activity and stability of ORR and OER.

Benefits of technology

It has achieved low-cost and efficient catalytic activity and stability of ORR and OER, and is suitable for flexible zinc-air batteries, promoting the development of high-performance flexible energy storage devices, and complying with the "dual carbon" goal.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119208634A_ABST
    Figure CN119208634A_ABST
Patent Text Reader

Abstract

The invention belongs to the technical field of oxygen electro-catalytic materials, and particularly relates to a high-entropy monatomic / cluster-loaded carbon nanofiber oxygen catalyst and a preparation method thereof. The preparation method comprises the following steps: S1, preparing ZIF-8 nanoparticles; s2, preparing a composite MOFs (Metal-Organic Frameworks) material on the basis of the ZIF-8 nanoparticles; s3, dispersing the composite MOFs material in a dimethylformamide solvent, adding Ni (NO3) 2.6 H2O and CuSO4. 5H2O, stirring to obtain a mixed solution C, dissolving a polyacrylonitrile polymer in the mixed solution C to prepare a spinning solution, and obtaining a micro-nano fiber membrane through an electrostatic spinning technology; s4, carrying out pre-oxidation and high-temperature carbonization treatment on the micro-nano fiber membrane to obtain a micro-nano carbon fiber membrane; and S5, anchoring Fe metal on the micro-nano carbon fiber membrane by adopting a chemical vapor deposition technology to obtain the high-entropy-loaded single atom / cluster carbon nanofiber oxygen catalyst.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of oxygen electrocatalytic materials, and in particular relates to a high-entropy single atom / cluster carbon nanofiber oxygen catalyst and a preparation method thereof. Background Art

[0002] Against the backdrop of the increasingly prominent global climate change problem, the development of zinc-air batteries with high energy density, long life and good flexibility is of great significance to promoting the practical application of flexible wearable electronic devices and achieving the goal of "carbon peak and carbon neutrality". At present, the reaction kinetics of ORR and OER in the positive electrode of zinc-air batteries are slow and the cycle stability is poor, which limits its large-scale application. Platinum-based catalysts (Pt / C, etc.) and iridium / ruthenium-based catalysts (Ir / C, RuO2, etc.) are the most effective ORR and OER catalysts in commercial use, respectively, but these precious metals are expensive and scarce. Therefore, it is urgent to develop a low-cost, efficient and stable bifunctional oxygen catalyst to replace precious metal catalysts.

[0003] Single atom catalysts (SACs) have become a research hotspot in the fields of ORR, OER, carbon dioxide reduction (CO2RR), nitrogen reduction (N2RR), hydrogen production (HER) and energy storage due to their unique atomic configuration and high atomic utilization. However, the existing single atom catalysts have a single structure, limited controllability of structural composition, and lack of synergy between metal atoms, making it difficult to achieve high catalytic activity and stability for both ORR and OER. At the same time, as one of the most core parts of zinc-air batteries, flexible air cathodes should have good flexibility in addition to good bifunctional oxygen catalytic performance. However, the current air cathodes are mostly powdered active substances coated on a conductive substrate, and their flexibility and structural stability are poor. Summary of the invention

[0004] In view of the shortcomings of the prior art, the present invention prepared high-entropy single atom / cluster carbon nanofiber oxygen catalysts through electrospinning, high-temperature carbonization and chemical vapor deposition strategies, and developed a carbon fiber catalytic material with high ORR / OER catalytic activity and stability and good flexibility, which is of great significance to promoting its practical application in high-efficiency energy storage devices such as flexible zinc-air batteries.

[0005] The purpose of the present invention can be achieved through the following technical solutions: A method for preparing a high entropy single atom / cluster carbon nanofiber oxygen catalyst, the preparation method comprising the following steps: S1. Add a methanol solution containing 2-methylimidazole to a methanol solution containing Zn(NO3)2·6H2O, and stir magnetically at room temperature for 24 hours; then wash with methanol for 3 times, and then centrifuge and vacuum dry to obtain ZIF-8 nanoparticles; S2. Add ZIF-8 nanoparticles to a methanol solution and obtain a uniform mixed solution A after ultrasonic and magnetic stirring; add a methanol solution containing 2-methylimidazole to the mixed solution A, and form a homogeneous mixed solution B after magnetic stirring; then add a methanol solution containing Zn(NO3)2·6H2O and Co(NO3)2·6H2O to the mixed solution B, and magnetically stir for 12 hours; then wash with methanol three times, and then obtain composite MOFs by centrifugation and vacuum drying; S3, dispersing the composite MOFs in a dimethylformamide solvent, then adding Ni(NO3)2·6H2O and CuSO4·5H2O, and obtaining a homogeneous mixed solution C after magnetic stirring, and then dissolving the polyacrylonitrile polymer in the mixed solution C to prepare a spinning solution, and then obtaining a porous micro-nano fiber membrane by electrospinning technology; S4, subjecting the micro-nano fiber membrane to pre-oxidation and high-temperature carbonization treatment in sequence to obtain a micro-nano carbon fiber membrane loaded with Zn, Co, Ni, and Cu metals; S5. Using chemical vapor deposition technology, Fe metal is anchored on the micro-nano carbon fiber membrane loaded with Zn, Co, Ni, and Cu metals to obtain a high-entropy single atom / cluster carbon nanofiber oxygen catalyst; In step S5, the Fe metal is anhydrous ferric chloride, and the mass ratio of the micro-nano carbon fiber membrane loaded with Zn, Co, Ni, and Cu metals to the anhydrous ferric chloride is 1:1.

[0006] Furthermore, in step S1, the mass ratio of 2-methylimidazole to Zn(NO3)2·6H2O is 1~3:1.

[0007] Furthermore, in step S2, the mass ratio of ZIF-8 nanoparticles, 2-methylimidazole, Zn(NO3)2·6H2O and Co(NO3)2·6H2O is (2~5):(16~48):(1~20):1.

[0008] Furthermore, the conditions for the centrifugal treatment in steps S1 and S2 are both: a rotation speed of 6000 rpm, a temperature of 15°C, and a time of 6 min; the conditions for the drying treatment in steps S1 and S2 are both: a temperature of 70°C and a time of 12 h.

[0009] Furthermore, in step S3, the mass ratio of the composite MOFs material, Ni(NO3)2·6H2O, CuSO4·5H2O and polyacrylonitrile polymer is (100~250):(1~5):1:(60~150).

[0010] Furthermore, the conditions of the electrospinning technology in step S3 are: voltage of 18 KV; solution flow rate of 1 mL / h; distance from the needle to the receiving device of 12 cm; ambient humidity of 45±5%.

[0011] Furthermore, the specific steps of pre-oxidation and high-temperature carbonization treatment in step S4 are: placing the micro-nano fiber membrane in a tubular furnace, heating it to 280 °C at a rate of 2 °C / min and keeping it warm for 2 h for pre-oxidation; then heating it to 920 °C at a rate of 5 °C / min in an argon environment and keeping it warm for 3 h for high-temperature carbonization treatment, and after natural cooling, a micro-nano carbon fiber membrane loaded with Zn, Co, Ni, and Cu metals is obtained.

[0012] Furthermore, in step S5, the Fe metal is anhydrous ferric chloride, and the mass ratio of the micro-nano carbon fiber membrane loaded with Zn, Co, Ni, and Cu metals to anhydrous ferric chloride is 1:0.5-2.

[0013] A high entropy single atom / cluster carbon nanofiber oxygen catalyst is prepared by the above-mentioned preparation method of the high entropy single atom / cluster carbon nanofiber oxygen catalyst.

[0014] The application of the above-mentioned high-entropy single atom / cluster carbon nanofiber oxygen catalyst in electrocatalytic oxygen reduction reaction and electrocatalytic oxygen evolution reaction.

[0015] Beneficial effects of the present invention: The preparation method of the high-entropy single atom / cluster carbon nanofiber oxygen catalyst proposed in the present invention uses electrospinning technology to prepare micro-nano fibers with multi-level pore structure and large specific surface area; the method uses high-temperature carbonization and chemical vapor deposition strategies to achieve uniform anchoring of transition metal single atoms / clusters such as Zn, Co, Ni, Cu and Fe on flexible micro-nano carbon fibers; the low-cost high-entropy transition metal single atom / cluster carbon nanofiber oxygen catalyst prepared by the method has high catalytic activity and stability for both ORR and OER, and can form good economic benefits. Therefore, using it as a flexible self-supporting material in zinc-air batteries is of great significance to promoting the development of high-performance flexible energy storage devices and achieving my country's "dual carbon" goals. BRIEF DESCRIPTION OF THE DRAWINGS

[0016] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, for ordinary technicians in this field, other drawings can be obtained based on these drawings without paying any creative work.

[0017] Figure 1 The scanning electron microscope (SEM) images of the high entropy single atom / cluster carbon nanofiber oxygen catalysts prepared in Examples 1 to 3 of the present invention include a, Example 1; b, Example 2; and c, Example 3.

[0018] Figure 2The transmission electron microscope (TEM) image of the high entropy single atom / cluster carbon nanofiber oxygen catalyst prepared in Example 1 of the present invention and the element distribution (EDS-mapping) image of the corresponding area.

[0019] Figure 3 This is a photo of a physical sample of the high entropy single atom / cluster carbon nanofiber oxygen catalyst prepared in Example 1 of the present invention.

[0020] Figure 4 This is a curved display diagram of the high entropy single atom / cluster carbon nanofiber oxygen catalyst prepared in Example 1 of the present invention.

[0021] Figure 5 X-ray diffraction (XRD) diagrams of high entropy single atom / cluster carbon nanofiber oxygen catalysts prepared in Examples 1 to 3 of the present invention, including a, Example 1; b, Example 2; c, Example 3.

[0022] Figure 6 The cyclic voltammetry (CV) curves of ORR of the high entropy single atom / cluster carbon nanofiber oxygen catalyst prepared in Examples 1 to 3 of the present invention in 0.1 M KOH electrolyte include (a) Example 1; (b) Example 2; (c) Example 3.

[0023] Figure 7 The linear sweep voltammetry (LSV) curves of the high entropy single atom / cluster carbon nanofiber oxygen catalyst prepared in Examples 1 to 3 of the present invention for ORR in 0.1 MKOH electrolyte at different rotation speeds, and the inset is the corresponding KL curve of ORR. They include (a) Example 1; (b) Example 2; (c) Example 3.

[0024] Figure 8 The LSV curves of the high entropy single atom / cluster carbon nanofiber oxygen catalysts prepared in Examples 1 to 3 of the present invention in the OER at 1600 rpm in 0.1 MKOH electrolyte, including (a), Example 1; (b), Example 2; (c), Example 3.

[0025] Fig. 9 The Tafel slope diagrams corresponding to the ORR of the high entropy single atom / cluster carbon nanofiber oxygen catalysts prepared in Examples 1 to 3 of the present invention in 0.1 M KOH electrolyte include a, Example 1; b, Example 2; c, Example 3.

[0026] Fig.10 The Tafel slope diagrams corresponding to the OER of the high entropy single atom / cluster carbon nanofiber oxygen catalysts prepared in Examples 1 to 3 of the present invention in 0.1 M KOH electrolyte include a, Example 1; b, Example 2; c, Example 3.

[0027] Fig.11 This is a stability test graph of ORR of the high entropy single atom / cluster carbon nanofiber oxygen catalyst prepared in Example 1 of the present invention and the commercial Pt / C catalyst in 0.1 M KOH electrolyte.

[0028] Fig.12 These are SEM images of low / medium / high entropy single atom / cluster carbon nanofiber oxygen catalysts prepared in Comparative Examples 1 to 4 of the present invention, including a, Comparative Example 1; b, Comparative Example 2; c, Comparative Example 3; d, Comparative Example 4.

[0029] Fig.13 XRD diagrams of low / medium / high entropy single atom / cluster carbon nanofiber oxygen catalysts prepared in Comparative Examples 1 to 4 of the present invention, including a, Comparative Example 1; b, Comparative Example 2; c, Comparative Example 3; d, Comparative Example 4.

[0030] Fig.14 LSV curves of the low / medium / high entropy single atom / cluster carbon nanofiber oxygen catalysts prepared in Comparative Examples 1 to 4 of the present invention and the commercial Pt / C catalyst for ORR in 0.1 M KOH electrolyte at 1600 rpm, including a, Comparative Example 1; b, Comparative Example 2; c, Comparative Example 3; d, Comparative Example 4; the illustration corresponds to the commercial Pt / C catalyst.

[0031] Fig.15 The Tafel slope graphs corresponding to the ORR of the low / medium / high entropy single atom / cluster carbon nanofiber oxygen catalysts prepared in Comparative Examples 1 to 4 of the present invention and the commercial Pt / C catalyst in 0.1 M KOH electrolyte include a, Comparative Example 1; b, Comparative Example 2; c, Comparative Example 3; d, Comparative Example 4; e, commercial Pt / C catalyst.

[0032] Fig.16 LSV curves of the low / medium / high entropy single atom / cluster carbon nanofiber oxygen catalysts prepared in Comparative Examples 1 to 4 of the present invention and the commercial RuO2 catalyst for OER at 1600 rpm in 0.1 M KOH electrolyte, including a, Comparative Example 1; b, Comparative Example 2; c, Comparative Example 3; d, Comparative Example 4; the illustration corresponds to the commercial RuO2 catalyst.

[0033] Fig.17 The Tafel slope diagrams corresponding to OER of low / medium / high entropy single atom / cluster carbon nanofiber oxygen catalysts and commercial RuO2 catalysts prepared in Comparative Examples 1 to 4 of the present invention in 0.1 M KOH electrolyte include a, Comparative Example 1; b, Comparative Example 2; c, Comparative Example 3; d, Comparative Example 4; e, commercial RuO2 catalyst. DETAILED DESCRIPTION

[0034] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0035] Commercial sources of commercial precious metal RuO2 catalysts and Pt / C catalysts are as follows: 1. Commercial precious metal Pt / C catalyst: Purchased from: Beijing Innochem Technology Co., Ltd. - Innochem; Product model: CAS number: 7440-06-4; Specification: 1g; Molecular weight: 195.08; No.:A07498; Batch number:KYGKQ03.

[0036] 2. Commercial precious metal RuO2 catalyst: Purchased by: Anhui Zesheng Technology Co., Ltd.-Annaiji Chemical; Product model: CAS number: 12036-10-1; Specification: 1g; Molecular weight: 133.07; No.:E060248; Batch number: 03INROMO.

[0037] Example 1 1. This example demonstrates a high entropy single atom / cluster carbon nanofiber oxygen catalyst (ZnCo-Ni 1.5 The preparation method of Cu-Fe@PCF comprises the following steps: S1. Synthesis of metal organic framework (ZIF-8): 200 mL of methanol solution containing 20 g of 2-methylimidazole was added to 200 mL of methanol solution containing 10 g of Zn(NO3)2·6H2O and magnetically stirred at room temperature for 24 h; then washed three times with methanol and centrifuged (centrifugation parameters: 6000 rpm, 15 ℃, 6 min); the collected precipitate was dried in a vacuum oven at 70 ℃ for 12 h to obtain ZIF-8 nanoparticles (NPs).

[0038] S2. Synthesis of composite metal-organic frameworks (MOFs): 0.9 g ZIF-8 NPs were dispersed in 100 mL methanol solution, ultrasonicated for 10 min and then magnetically stirred; 8 g 2-methylimidazole was dissolved in 100 mL methanol solution, and the above solution was added and magnetically stirred for 10 min to form a homogeneous mixed solution; 4 g Zn(NO3)2·6H2O and Co(NO3)2·6H2O were dissolved in 100 mL methanol solution at a mass ratio of 15:1, and the above mixed solution was added and magnetically stirred for 3 h; then washed with methanol three times and centrifuged (centrifugation parameters: 6000 rpm, 15 ℃, 6 min); the collected precipitate was dried in a vacuum oven at 70 ℃ for 12 h to obtain ZIF-8+ZIF-67@ZIF-8 composite MOFs.

[0039] S3. Preparation of micro-nano fiber membrane: 0.8 g of the composite MOFs NPs synthesized in step (2) was dispersed in 4 g of DMF solvent, ultrasonicated for 30 min, and then magnetically stirred for 24 h; 9.75 mg of Ni(NO3)2·6H2O and 4.875 mg of CuSO4·5H2O were dissolved in 1 g of DMF, added to the above solution, and magnetically stirred for 1 h; 0.5 g of PAN was then added to the above mixed solution, and magnetically stirred for 12 h to obtain a homogeneous spinning solution; the obtained spinning solution was made into a micro-nano fiber membrane using electrospinning technology. The following are included: the mass ratio of composite MOFs and PAN is 1.6:1; the amount of Ni salt added is 1.5% of the remaining carbon content; the voltage of electrospinning is 18 KV; the solution flow rate is 1 mL / h; the distance from the needle to the receiving device is 12 cm; and the ambient humidity is 45±5%.

[0040] S4, micro-nano carbon fiber catalytic materials loaded with Zn, Co, Ni, and Cu metals (ZnCo-Ni 1.5 Preparation of Cu@PCF): The micro-nano fiber membrane prepared in step (3) was placed in a tubular furnace, heated to 280 °C at a rate of 2 °C / min and kept at this temperature for 2 h for pre-oxidation; then heated to 920 °C at a rate of 5 °C / min in an argon (Ar) environment and kept at this temperature for 3 h, and then cooled naturally to obtain ZnCo-Ni 1.5 Cu@PCF.

[0041] S5, Zn, Co, Ni, Cu, Fe high entropy single atom / cluster carbon nanofiber oxygen catalyst (ZnCo-Ni 1.5 Preparation of Cu-Fe@PCF: ZnCo-Ni prepared in step (4) 1.5Cu@PCF micro-nano carbon fiber membrane and anhydrous ferric chloride (FeCl3) of equal mass were placed in a tubular furnace, with FeCl3 at the upstream and the fiber membrane at the downstream. The CVD technology was used to heat the mixture to 750°C at a rate of 10°C / min in an Ar atmosphere and then keep the temperature for 3 h for vapor deposition. High entropy single atom / cluster carbon nanofiber oxygen catalyst was obtained. The mass ratio of the micro-nano carbon fiber membrane loaded with Zn, Co, Ni, and Cu metals to anhydrous ferric chloride is 1:1.

[0042] 2. ZnCo-Ni obtained by the above preparation method and process parameters 1.5 The structural performance test results of Cu-Fe@PCF are as follows: (a) Morphological structure: Figure 1 From the SEM image in a, it can be observed that the composite MOFs-derived carbon nanocages are evenly distributed on the carbon fibers, where the diameter of the carbon fibers is about 2 µm, the size of the MOFs-derived carbon nanocages is about 300-400 nm, and the carbon fibers have a multi-level micro-nano structure. Figure 2 From the TEM images and EDS-mapping images of the corresponding areas, it can be observed that the metal species coexist as single atoms and nanoclusters, where the size of the nanoclusters / small nanoparticles is about 10 nm. Figure 3 ZnCo-Ni 1.5 Physical sample photo of Cu-Fe@PCF. Figure 4 ZnCo-Ni 1.5 The bending display of the Cu-Fe@PCF sample shows that the sample can maintain good integrity after being folded and bent for many times, indicating that ZnCo-Ni 1.5 Cu-Fe@PCF has good flexibility. Figure 5 The XRD pattern of ZnCo-Ni 1.5 The peak of Cu-Fe@PCF at about 26° corresponds to the (002) crystal plane of graphitic carbon, the peak at about 35° corresponds to the (311) crystal plane of Fe3O4, and the peak at about 45° corresponds to the (200) crystal plane of FeO, indicating the formation of some metal oxide clusters of iron species.

[0043] (b) Catalytic performance: 5 mg ZnCo-Ni 1.5Cu-Fe@PCF catalyst powder was dispersed in 1.025 mL of a mixed solution containing 1 mL of ethanol / water (1:1, v / v) and 25 µL of Nafion (5 wt.%). The mixture was subjected to low temperature ultrasound for 30 min to form a homogeneous catalyst ink. 20 µL of the ink was dropped on the surface of a glassy carbon electrode and dried to obtain a working electrode. The working electrode was tested in a 0.1 M KOH solution using a standard three-electrode system with a stone mill as the counter electrode and Ag / AgCl as the reference electrode. A rotating disk electrode (RDE) was used at 50 mV s -1 The CV curves were obtained at a scan rate of 5 mV s -1 The ORR-LSV curves were obtained at scan rates of 400, 625, 900, 1225, and 1600 rpm. The OER-LSV curves were measured at a scan rate of 1600 rpm in 0.1 M KOH solution. Figure 6 As shown in (a), ZnCo-Ni 1.5 The CV curve of Cu-Fe@PCF has an obvious oxygen reduction peak at 0.808 V. Figure 7 As shown in (a), in alkaline medium, ZnCo-Ni 1.5 The ORR half-wave potential (E1 / 2) of Cu-Fe@PCF is 0.864 V, which is higher than that of commercial precious metal Pt / C (0.850 V). The KL equation corresponding to the inset shows that it performs ORR via a 4-electron transfer pathway. Figure 8 As shown in (a), at 10 mA cm -2 ZnCo-Ni 1.5 The OER overpotential of Cu-Fe@PCF is 1.550 V, which is better than that of the commercial noble metal RuO2 (1.602 V). Fig. 9 As shown in a, ZnCo-Ni 1.5 The ORR Tafel slope of Cu-Fe@PCF is 86 mV dec -1 , which is smaller than that of Pt / C catalyst (107 mV dec -1 ), indicating faster ORR reaction kinetics. Fig.10 As shown in a, ZnCo-Ni 1.5 The OER Tafel slope of Cu-Fe@PCF is 83 mV dec -1 , which is smaller than that of RuO2 catalyst (91 mV dec -1 ), indicating that the catalyst has a faster OER kinetic reaction rate. Fig.11 As shown in the figure, after a 12 h continuous stability test at a potential of 0.7 V, ZnCo-Ni 1.5The current retention rate of Cu-Fe@PCF is 92.3%, which is higher than that of Pt / C catalyst (86.6%).

[0044] From the above test results, it can be seen that the high entropy single atom / cluster carbon nanofiber oxygen catalyst (ZnCo-Ni 1.5 Cu-Fe@PCF) has excellent ORR and OER catalytic activity and stability, which are better than commercial precious metal Pt / C and RuO2 catalysts, respectively. In addition, the fiber catalyst has good flexibility and can be used in the air positive electrode of flexible zinc-air batteries.

[0045] Example 2 1. This example demonstrates a high entropy single atom / cluster carbon nanofiber oxygen catalyst (ZnCo-Ni 2.0 The preparation method of Cu-Fe@PCF is basically the same as that of Example 1, except that 9.75 mg of Ni(NO3)2·6H2O in step (3) is replaced by 13 mg of Ni(NO3)2·6H2O, so that the amount of Ni salt added is 2.0% of the remaining carbon content.

[0046] 2. ZnCo-Ni obtained by the above preparation method and process parameters 2.0 The structural performance test results of Cu-Fe@PCF are as follows: (a) Morphological structure: Figure 1 The SEM image in b shows that the composite MOFs-derived carbon nanocages are evenly distributed on the carbon fiber, where the diameter of the carbon fiber is about 1.5 µm, the size of the MOFs-derived carbon nanocages is about 400 nm, and the carbon fiber has a multi-level micro-nano structure. Through the TEM image and the EDS-mapping image of the corresponding area, it can be observed that the metal species coexist as single atoms and nanoclusters, where the size of the nanoclusters / small nanoparticles is about 10 nm. The sample was folded and bent several times, and it was able to maintain good integrity, indicating that ZnCo-Ni 2.0 Cu-Fe@PCF has good flexibility. Figure 5 In the XRD pattern of b, it can be observed that ZnCo-Ni 2.0 The peak of Cu-Fe@PCF at about 26° corresponds to the (002) crystal plane of graphitic carbon, the peaks at about 35° and 63° correspond to the (311) and (511) crystal planes of Fe3O4, respectively, the peak at about 45° corresponds to the (200) crystal plane of FeO, and the peak at about 55° corresponds to the (220) crystal plane of Ni, indicating the formation of metal oxide clusters of some iron species.

[0047] (b) Catalytic performance: The test method of this embodiment is basically the same as that of embodiment 1, except that ZnCo-Ni 2.0Cu-Fe@PCF was used as the working electrode for catalytic testing. Figure 6 As shown in (b), ZnCo-Ni 2.0 The CV curve of Cu-Fe@PCF has an obvious oxygen reduction peak at 0.803 V. Figure 7 As shown in (b), in alkaline medium, ZnCo-Ni 2.0 ORR half-wave potential (E 1 / 2 ) is 0.839 V. The KL equation corresponding to the inset shows that ORR occurs via a 4-electron transfer pathway. Figure 8 As shown in (b), at 10 mA cm -2 ZnCo-Ni 2.0 The OER overpotential of Cu-Fe@PCF is 1.630 V. Fig. 9 As shown in b, ZnCo-Ni 2.0 The ORR Tafel slope of Cu-Fe@PCF is 74 mV dec -1 , which is less than that of Pt / C catalyst (107 mVdec -1 ), indicating faster ORR reaction kinetics. Fig.10 As shown in b, ZnCo-Ni 2.0 The OER Tafel slope of Cu-Fe@PCF is 118 mV dec -1 , which is at a relatively low level. After a 12-h continuous stability test at 0.7 V potential, ZnCo-Ni 2.0 The current retention rate of Cu-Fe@PCF is close to 100%.

[0048] Example 3 1. This example demonstrates a high entropy single atom / cluster carbon nanofiber oxygen catalyst (ZnCo-Ni 2.5 The preparation method of Cu-Fe@PCF is basically the same as that of Example 1, except that 9.75 mg of Ni(NO3)2·6H2O in step (3) is replaced by 16.25 mg of Ni(NO3)2·6H2O, so that the amount of Ni salt added is 2.5% of the remaining carbon content.

[0049] 2. ZnCo-Ni obtained by the above preparation method and process parameters 2.5 The structural performance test results of Cu-Fe@PCF are as follows: (a) Morphological structure: Figure 1The SEM image in c shows that the composite MOFs-derived carbon nanocages are evenly distributed on the carbon fiber, where the diameter of the carbon fiber is about 2 µm, the size of the MOFs-derived carbon nanocages is about 400 nm, and the carbon fiber has a multi-level micro-nano structure. Through the TEM image and the EDS-mapping image of the corresponding area, it can be observed that the metal species coexist as single atoms and nanoclusters, where the size of the nanoclusters / small nanoparticles is about 10 nm. The sample was folded and bent several times, and it was able to maintain good integrity, indicating that ZnCo-Ni 2.5 Cu-Fe@PCF has good flexibility. Figure 5 The XRD pattern of ZnCo-Ni 2.5 The peak of Cu-Fe@PCF at about 26° corresponds to the (002) crystal plane of graphitic carbon, the peak at about 45° corresponds to the (200) crystal plane of FeO, the peak at about 55° corresponds to the (220) crystal plane of Ni, and the peak at about 63° corresponds to the (511) crystal plane of Fe3O4, indicating the formation of some metal oxide clusters of iron species.

[0050] (b) Catalytic performance: The test method of this embodiment is basically the same as that of embodiment 1, except that ZnCo-Ni 2.5 Cu-Fe@PCF was used as the working electrode for catalytic testing. Figure 6 As shown in (c), ZnCo-Ni 2.5 The CV curve of Cu-Fe@PCF has an obvious oxygen reduction peak at 0.787 V. Figure 7 As shown in (c), in alkaline medium, ZnCo-Ni 2.5 ORR half-wave potential (E 1 / 2 ) is 0.834 V. The KL equation corresponding to the inset shows that ORR occurs via a 4-electron transfer pathway. Figure 8 As shown in (c), at 10 mA cm -2 ZnCo-Ni 2.5 The OER overpotential of Cu-Fe@PCF is 1.635 V. Fig. 9 As shown in c, ZnCo-Ni 2.5 The ORR Tafel slope of Cu-Fe@PCF is 71 mV dec -1 , which is less than that of Pt / C catalyst (107 mVdec -1 ), indicating faster ORR reaction kinetics. Fig.10 As shown in c, ZnCo-Ni 2.5 The OER Tafel slope of Cu-Fe@PCF is 121 mV dec -1, which is at a relatively low level. After a 12-h continuous stability test at 0.7 V potential, ZnCo-Ni 2.5 The current retention rate of Cu-Fe@PCF is close to 100%.

[0051] Comparative Example 1 1. This comparative example provides a method for preparing an iron-supported single-atom carbon nanofiber oxygen catalyst (ZIF-8, Fe@PCF), which is basically the same as Example 1, except that: 0.8 g of the ZIF-8 synthesized in step (1) is dispersed in 5 g of DMF solvent, ultrasonicated for 30 min, and then magnetically stirred for 24 h; then 0.5 g of PAN is added, and magnetically stirred for 12 h to obtain a homogeneous spinning solution; the spinning solution is made into a micro-nano fiber membrane by using electrospinning technology; and the micro-nano fiber membrane is subjected to high-temperature carbonization in step (4) to obtain PCF; and then chemical vapor deposition is performed in step (5) to deposit the ZnCo-Ni 1.5 By replacing Cu@PCF with PCF, we can get ZIF-8,Fe@PCF.

[0052] 2. The structural performance test results of ZIF-8 and Fe@PCF obtained by the above preparation method and process parameters are as follows: Fig.12 The SEM image shown in a shows that the ZIF-8 derived carbon nanocages are evenly distributed on the carbon fibers, where the diameter of the carbon fibers is about 1.5 µm, the size of the ZIF-8 derived carbon nanocages is about 200-300 nm, and the carbon fibers have a multi-level micro-nano structure. The loaded ZIF-8 derived carbon nanocages collapse after high-temperature carbonization by CVD. Fig.13 From the XRD pattern of a, we can observe that the peak of ZIF-8, Fe@PCF at about 26° corresponds to the (002) crystal plane of graphite carbon, and the peak at about 45° corresponds to the (200) crystal plane of FeO. Fig.14 As shown in (a), the ORR half-wave potential (E 1 / 2 ) is 0.843 V. Fig.15 As shown in (a), the ORR Tafel slope of ZIF-8,Fe@PCF is 77 mV dec -1 , which is less than that of Pt / C catalyst (107 mVdec -1 ), indicating faster ORR reaction kinetics. Fig.16 As shown in Fig. 1a, the OER overpotential of ZIF-8,Fe@PCF is 1.682 V at 10 mA cm-2. Fig.17 As shown in (a), the OER Tafel slope of ZIF-8 and Fe@PCF is 111 mV dec. -1 , which is at a relatively low level.

[0053] Comparative Example 2 1. This comparative example provides a carbon nanofiber oxygen catalyst (ZnCo-Ni 1.5 The preparation method of Cu@PCF is basically the same as that of Example 1, except that: ZnCo-Ni 1.5 Cu@PCF does not require step (5). 2. ZnCo-Ni obtained by the above preparation method and process parameters 1.5 The structural performance test results of Cu@PCF are as follows: Fig.12 The SEM image shown in (b) shows that the carbon nanocages derived from the composite MOFs are evenly distributed on the carbon fibers, where the diameter of the carbon fibers is about 1.5 µm, the size of the carbon nanocages derived from the composite MOFs is about 200-300 nm, and the carbon fibers have a multi-level micro-nano structure. Fig.13 In the XRD pattern of b, it can be observed that ZnCo-Ni 1.5 The peak of Cu@PCF at about 26° corresponds to the (002) crystal plane of graphite carbon, and the peak at about 45° corresponds to the (200) crystal plane of FeO. Fig.14 As shown in b, in alkaline medium, ZnCo-Ni 1.5 ORR half-wave potential (E 1 / 2 ) is 0.811 V. Fig.15 As shown in b, ZnCo-Ni 1.5 The ORRTafel slope of Cu@PCF is 58 mV dec -1 , which is smaller than that of Pt / C catalyst (107 mV dec -1 ), indicating faster ORR reaction kinetics. Fig.16 As shown in b, at 10 mA cm -2 ZnCo-Ni 1.5 The OER overpotential of Cu@PCF is 1.749 V. Fig.17 As shown in b, ZnCo-Ni 1.5 The OER Tafel slope of Cu@PCF is 151 mV dec -1 .

[0054] Comparative Example 3 1. This comparative example provides a high entropy single atom / cluster carbon nanofiber oxygen catalyst (ZnCo-Ni 1.5 Cu-Fe 0.5 The preparation method of @PCF is basically the same as that of Example 1, except that the medium-quality anhydrous ferric chloride (FeCl3) in step (5) is replaced with 0.5 times the FeCl3.

[0055] 2. ZnCo-Ni obtained by the above preparation method and process parameters 1.5 Cu-Fe 0.5 The structural performance test results of @PCF are as follows: Fig.12 The SEM image shown in c shows that the carbon nanocages derived from the composite MOFs are evenly distributed on the carbon fibers, where the diameter of the carbon fibers is about 1.5 µm, the size of the carbon nanocages derived from the composite MOFs is about 300 nm, and the carbon fibers have a multi-level micro-nano structure. Fig.13 The XRD pattern of ZnCo-Ni 1.5 Cu-Fe 0.5 The peak of @PCF at about 26° corresponds to the (002) crystal plane of graphite carbon, the peak at about 35° corresponds to the (311) crystal plane of Fe3O4, and the peak at about 45° corresponds to the (200) crystal plane of FeO. Fig.14 As shown in c, in alkaline medium, ZnCo-Ni 1.5 Cu-Fe 0.5 @PCF ORR half-wave potential (E 1 / 2 ) is 0.832 V. Fig.15 As shown in c, ZnCo-Ni 1.5 Cu-Fe 0.5 The ORR Tafel slope of @PCF is 67 mV dec -1 , which is smaller than that of Pt / C catalyst (107 mV dec -1 ), indicating faster ORR reaction kinetics. Fig.16 As shown in c, at 10 mA cm -2 ZnCo-Ni 1.5 Cu-Fe 0.5 The OER overpotential of @PCF is 1.673 V. Fig.17 As shown in c, ZnCo-Ni 1.5 Cu-Fe 0.5 @PCF’s OER Tafel slope is 104 mV dec -1 , which is at a relatively low level.

[0056] Comparative Example 4 1. This comparative example provides a high entropy single atom / cluster carbon nanofiber oxygen catalyst (ZnCo-Ni 1.5 Cu-Fe 2.0 The preparation method of @PCF is basically the same as that of Example 1, except that the medium-quality anhydrous ferric chloride (FeCl3) in step (5) is replaced with 2.0 times the FeCl3.

[0057] 2. ZnCo-Ni obtained by the above preparation method and process parameters 1.5 Cu-Fe 2.0 The structural performance test results of @PCF are as follows: Fig.12 The SEM image shown in (d) shows that the composite MOFs-derived carbon nanocages are evenly distributed on the carbon fiber, where the diameter of the carbon fiber is about 1 µm, the size of the composite MOFs-derived carbon nanocages is about 300 nm, and the carbon fiber has a multi-level micro-nano structure. The composite MOFs-derived carbon nanocages loaded thereon collapse after high-temperature carbon sintering by CVD. Fig.13 The XRD pattern of ZnCo-Ni 1.5 Cu-Fe 2.0 The peak of @PCF at about 26° corresponds to the (002) crystal plane of graphite carbon, the peak at about 35° corresponds to the (311) crystal plane of Fe3O4, and the peak at about 45° corresponds to the (200) crystal plane of FeO. Fig.14 As shown in (d), in alkaline medium, ZnCo-Ni 1.5 Cu-Fe 2.0 @PCF ORR half-wave potential (E 1 / 2 ) is 0.850 V. Fig.15 As shown in (d), ZnCo-Ni 1.5 Cu-Fe 2.0 @PCF ORR Tafel slope is 81 mV dec -1 , which is smaller than that of Pt / C catalyst (107 mV dec -1 ), indicating faster ORR reaction kinetics. Fig.16 As shown in (d), at 10 mA cm -2 ZnCo-Ni 1.5 Cu-Fe 2.0 The OER overpotential of @PCF is 1.590 V. Fig.17 As shown in (d), ZnCo-Ni 1.5 Cu-Fe 2.0 @PCF’s OER Tafel slope is 84 mVdec -1 , which is at a relatively low level.

[0058] In the description of this specification, the description with reference to the terms "one embodiment", "one comparative example", "specific example", etc. means that the specific features, structures, materials or characteristics described in conjunction with the embodiment or comparative example are included in at least one embodiment or comparative example of the present invention. In this specification, the schematic representation of the above terms does not necessarily refer to the same embodiment or comparative example. Moreover, the specific features, structures, materials or characteristics described can be combined in any one or more embodiments or comparative examples in a suitable manner.

[0059] The above shows and describes the basic principles, main features and advantages of the present invention. It should be understood by those skilled in the art that the present invention is not limited by the above embodiments and comparative examples, and the above embodiments and descriptions are only for explaining the principles of the present invention. Without departing from the spirit and scope of the present invention, the present invention may have various changes and improvements, and these changes and improvements all fall within the scope of the present invention to be protected.

Claims

1. A method for preparing a high entropy single atom / cluster carbon nanofiber oxygen catalyst, characterized in that: The preparation method comprises the following steps: S1. Add a methanol solution containing 2-methylimidazole to a methanol solution containing Zn(NO3)2·6H2O, and stir magnetically at room temperature for 24 hours; then wash with methanol for 3 times, and then centrifuge and vacuum dry to obtain ZIF-8 nanoparticles; S2. Add ZIF-8 nanoparticles to a methanol solution and obtain a uniform mixed solution A after ultrasonic and magnetic stirring; add a methanol solution containing 2-methylimidazole to the mixed solution A, and form a homogeneous mixed solution B after magnetic stirring; then add a methanol solution containing Zn(NO3)2·6H2O and Co(NO3)2·6H2O to the mixed solution B, and magnetically stir for 12 hours; then wash with methanol three times, and then obtain composite MOFs by centrifugation and vacuum drying; S3, dispersing the composite MOFs in a dimethylformamide solvent, then adding Ni(NO3)2·6H2O and CuSO4·5H2O, and obtaining a homogeneous mixed solution C after magnetic stirring, and then dissolving the polyacrylonitrile polymer in the mixed solution C to prepare a spinning solution, and then obtaining a porous micro-nano fiber membrane by electrospinning technology; S4, subjecting the micro-nano fiber membrane to pre-oxidation and carbonization treatment in sequence to obtain a micro-nano carbon fiber membrane loaded with Zn, Co, Ni, and Cu metals; S5. Using chemical vapor deposition technology, Fe metal is anchored on the micro-nano carbon fiber membrane loaded with Zn, Co, Ni, and Cu metals to obtain a high-entropy single atom / cluster carbon nanofiber oxygen catalyst; In step S5, the Fe metal is anhydrous ferric chloride, and the mass ratio of the micro-nano carbon fiber membrane loaded with Zn, Co, Ni, and Cu metals to the anhydrous ferric chloride is 1:

1.

2. The method for preparing the high entropy single atom / cluster carbon nanofiber oxygen catalyst according to claim 1, characterized in that: In step S1, the mass ratio of 2-methylimidazole to Zn(NO3)2·6H2O is 1~3:

1.

3. The method for preparing the high entropy single atom / cluster carbon nanofiber oxygen catalyst according to claim 1, characterized in that: In step S2, the mass ratio of ZIF-8 nanoparticles, 2-methylimidazole, Zn(NO3)2·6H2O and Co(NO3)2·6H2O is (2~5):(16~48):(1~20):

1.

4. The method for preparing the high entropy single atom / cluster carbon nanofiber oxygen catalyst according to claim 1, characterized in that: The conditions for the centrifugal treatment in steps S1 and S2 are both: a rotation speed of 6000 rpm, a temperature of 15°C, and a time of 6 min; the conditions for the drying treatment in steps S1 and S2 are both: a temperature of 70°C, and a time of 12 h.

5. The method for preparing the high entropy single atom / cluster carbon nanofiber oxygen catalyst according to claim 1, characterized in that: In step S3, the mass ratio of the composite MOFs material, Ni(NO3)2·6H2O, CuSO4·5H2O and polyacrylonitrile polymer is (100~250):(1~5):1:(60~150).

6. The method for preparing the high entropy single atom / cluster carbon nanofiber oxygen catalyst according to claim 1, characterized in that: The conditions of the electrospinning technology in step S3 are: voltage of 18 KV; solution flow rate of 1 mL / h; distance from the needle to the receiving device of 12 cm; ambient humidity of 45±5%.

7. The method for preparing the high entropy single atom / cluster carbon nanofiber oxygen catalyst according to claim 1, characterized in that: The specific steps of pre-oxidation and carbonization treatment in step S4 are as follows: the micro-nano fiber membrane is placed in a tubular furnace, and the temperature is increased to 280 °C at a rate of 2 °C / min and kept at this temperature for 2 h for pre-oxidation; then the temperature is increased to 920 °C at a rate of 5 °C / min in an argon environment and kept at this temperature for 3 h for high-temperature carbonization treatment, and a micro-nano carbon fiber membrane loaded with Zn, Co, Ni, and Cu metals is obtained after natural cooling.

8. A high entropy single atom / cluster carbon nanofiber oxygen catalyst, characterized in that: The catalyst is prepared by the method for preparing the high entropy single atom / cluster carbon nanofiber oxygen catalyst according to any one of claims 1 to 7.

9. Use of the high entropy single atom / cluster carbon nanofiber oxygen catalyst as claimed in claim 8 in electrocatalytic oxygen reduction reaction and electrocatalytic oxygen evolution reaction.

Citation Information

Patent Citations

  • Compound carbon-fiber membrane and preparation method thereof

    CN108855029A

  • Porous carbon-based nanofiber thin film material loaded by metal monatomic and metal derivative thereof as well as preparation method and application thereof

    CN113540478A

  • Bead-like cobalt-nitrogen co-doped carbon nanocage / carbon nanofiber composite catalyst and preparation method thereof

    CN114420958A

  • Iron-cobalt bimetal oxygen reduction electro-catalytic material as well as preparation method and application thereof

    CN114843536A

  • High-entropy alloy carbon nanofiber material as well as preparation method and application thereof

    CN117286632A

Cited By

  • Iron-nickel diatomic fiber catalyst with precise and adjustable local structure as well as preparation method and application of iron-nickel diatomic fiber catalyst

    CN121192183A